Hubungan Aktivitas Fisik dengan Kejadian Obesitas pada Usia Produktif di Wilayah Kerja Puskesmas Marina Permai Kota Palangka Raya: Relationship of Physical Activity with Obesity in Productive Age in the Working Area of the Marina Permai Puskesmas City Palangka Raya - Wiwin Agustina; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Obesity is the abnormal or excessive fat accumulation that poses a health risk. Obesity in productive age occurs because there is an imbalance between calorie intake and daily physical activity. Obesity is a risk factor for chronic diseases such as diabetes, hypertension, heart disease, and cancer. This study aimed to determine the relationship between physical activity and the incidence of obesity in productive age in the working area of Pukesmas Marina Permai. The prevalence of obesity in Indonesia in adults >18 from 2015-2019 has increased by 15.4%). The design of this study used an analytical observational quantitative method with a cross-sectional approach. The population in this study were all productive ages in the Marina Permai Public Health Center working area. The sample in this study is some of the productive ages, as many as 77 productive age with the sampling technique using purposive sampling. After tabulating the existing data, the research data was taken using a questionnaire and analyzed using the Chi-Square analysis test. The design of this study used a quantitative analytical observational method with the results showed that there was a relationship between physical activity and the incidence of obesity in productive age in the work area of the Marina Permai Public Health Center, Palangka Raya City (p-value = 0.002 a> = 0.05). Therefore, it is expected that productive age can increase daily physical activity.